Abolition of methacholine induced bronchoconstriction by the hyperventilation of exercise or volition. Issue 8 (August 1988) - Freedman, S; Lane, R; Gillett, M K; Guz, A
Abstract : Total pulmonary resistance was measured from continuous records of flow and oesophageal pressure in five normal subjects on three separate days before and after inhalation of methacholine. The dose of methacholine produced, on average, a fivefold increase in airway resistance. Immediately after methacholine inhalation the subjects underwent a progressive exercise test on a cycle ergometer (day 1) or voluntary hyperventilation (day 2) or remained resting (day 3). On the first day during exercise pulmonary resistance fell rapidly to baseline levels within two to three minutes and remained there for the 10 minute duration of the exercise. On day 2 voluntary reproduction of the same level and pattern of ventilation as during exercise resulted in a similar fall of resistance. On the third day, when the subjects remained at rest, pulmonary resistance remained raised for 10 minutes. It is concluded that the bronchodilator effects of exercise can be explained by the increased ventilation rather than the exercise itself, but with much smaller tidal volumes than have previously been thought necessary to reduce drug induced bronchoconstriction.